1996
DOI: 10.1093/pasj/48.3.425
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Spectroscopy of Centaurus X-3 with ASCA over an Eclipse

Abstract: The X-ray binary pulsar Cen X-3 was observed with the ASCA satellite over an entire binary eclipse. With unprecedented energy resolution at the iron K-energy band (FWHM ∼ 2%), three iron emission lines at 6.4 keV, 6.7 keV, and 6.97 keV were clearly resolved. At lower energies, lines from hydrogenic ions of Ne, Mg, Si, and S were also observed. Spectral variations over the eclipse were studied, in particular variations of the iron emission lines. Although the intensity of the 6.4 keV line, which is due to fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 0 publications
8
64
0
Order By: Relevance
“…Considering the equivalent width of the iron line, the optical depth is not much smaller than 0.1. Ebisawa et al (1996) reported that the optical depth was 0.52^0.10 from ASCA SIS data. Thus, we calculated the average delay of the iron band continuum from the original X-rays as…”
Section: Distance To the Reprocessormentioning
confidence: 99%
See 4 more Smart Citations
“…Considering the equivalent width of the iron line, the optical depth is not much smaller than 0.1. Ebisawa et al (1996) reported that the optical depth was 0.52^0.10 from ASCA SIS data. Thus, we calculated the average delay of the iron band continuum from the original X-rays as…”
Section: Distance To the Reprocessormentioning
confidence: 99%
“…Although we do not know the geometry of the reprocessor, it may cover more than half of the sphere (i.e., 2n steradian) as seen from the neutron star (Ebisawa et al 1996), and our derived delay time is the averaged delay time during the observation. Thus, we assume the spherical shell for the reprocessor and calculate the distance between neutron star and the reprocessor by simply multiplying our derived delay time by light velocity.…”
Section: Distance To the Reprocessormentioning
confidence: 99%
See 3 more Smart Citations